Analysis of Shopee Paylater Features and Twin Date Events On The Consumptive Behavior Of Tadulako University Students in E-Commerce Shopee - Kadoena, Friskha Anggriani; Wahyuningsih, Wahyuningsih; Sutomo, Maskuri; Rian Risendy (Quantitative Economics and Management Studies, 2024)
This research aims to analyze the role of using the Shopee PayLater feature and the twin date event on the consumer behavior of Shopee users. The sample in this study was selected using a purposive sampling technique, with the criteria being that respondents had activated the paylater feature on the Shopee application. The number of samples used was 90 respondents. Data analysis was carried out using the multiple linear regression method, with an Fcount test result of 12.263 which was greater than Ftable 3.10 and a significant value of 0.000 which was smaller than 0.05. These results indicate that the Shopee Paylater feature and the Twin Date Event simultaneously have an influence on consumer behavior. The R square value in this study reveals that 22% of the variability in consumer behavior is influenced by the Shopee Paylater feature and the Twin Date Event, while 78% is influenced by other variables not discussed in this study.